(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This paper focuses on the impact that blended learning has on the level of satisfaction experienced by learners and is carried out by MBA students who are enrolled in classes at a business school. The researcher would like to draw attention to three requirements for the research project, which are as follows: The first factor is the user's own subjective perception of the system; the second a person specific would require no and the third is the driving influences that effectively provide the learners with information. This study demonstrates how the parameters will influence the level of learning satisfaction experienced by students. Data collection: This study used a sample size of 100 business school students as respondents. There were only 88 non-corrupted data points available to the researcher, and so the hypothesis could only be tested to that extent. Interpretation: The structural equation modelling technique is emphasized for validation purposes in order to examine the relationship between latent variables. It demonstrates how effortlessly user perception can be manipulated. Learners' efficiency has a positive effect on users' perceptions of effortlessness and the quality of their experience. When students succeed, they feel more satisfied with their learning experience. The study's overarching goal is to establish which factors actually do have an impact on students' levels of contentment.